High-performance hydrophobic magnetic hydrotalcite for selective treatment of oily wastewater - Miotto Menino, Naiara (Environmental technology, 2023)
Oil emulsified in water is one of the most difficult mixtures to treat due to the good stability of emulsions, so there is a growing demand for more efficient methods for separating immiscible oil/water mixtures. In this context, the focus of this study was to obtain an adsorbent for the selective treatment of a simulated oily wastewater. To this aim, a modified hydrotalcite sample with hydrophobic and magnetic characteristics was prepared and characterized. Initially, the effect of sodium dodecyl sulfate (SDS) amount on the adsorbent characteristics was evaluated (266-800 mgSDS g-1LDH). The hydrophobic hydrotalcite (LDH-SDS) containing 533 mgSDS g-1LDH (LDH-SDS2) presented a higher interlayer space where the surfactant molecules were arranged perpendicular to the lamellae, allowing better access to the hydrotalcite pores and facilitating the selective adsorption of oil compounds. Moreover, the synergistic association of hydrophobic properties with super-wetting and effective adhesion oil to Fe3O4 favoured the selective adsorption of the simulated oily wastewater onto the hydrophobic and magnetic hydrotalcite (LDH-MSDS), facilitating the post-treatment separation. The kinetic analysis demonstrated that the adsorption equilibrium was attained in 120 min and the pseudo-second order model was the most suitable for predicting the removal of total organic carbon (TOC) from the simulated oily wastewater. The Langmuir model described very well the equilibrium experimental data, with a maximum adsorption capacity for TOC removal using LDH-MSDS of 659.9 mg g-1. Therefore, the modified hydrotalcite prepared in this study showed intrinsic characteristics that make it a promising adsorbent for the selective treatment of oily wastewaters